Consumer complaint behaviour, satisfaction with complaint handling, mobile phone dependency and relationship quality in mobile phone service industry - A. Rahman, Mohd. Khirzanbadzli (2016)
The insignificant number of complaints as compared to the huge number of mobile phone subscribers generated the interest to conduct this study.This study is related to consumer complaint behavior, relationship quality, satisfaction with complaint handling and mobile phone dependency in the mobile phone services industry.The main purpose of the study is to examine the relationship between consumer complaint behavior (CCB) and relationship quality. This study also examines the relationship between consumer complaint behavior and satisfaction with complaint handling as well as the relationship between satisfaction with complaint handling and relationship quality. Further, the role of satisfaction as mediator is also investigated in this study.Considering this study is involving mobile phone services users,the final aim of this study is to examine the Effects of mobile phone dependency as moderator on the hypothesized relationships. Social exchange theory,theory of exit, voice and loyalty, attachment theory as well as the results from previous studies were adopted in developing the framework for the study.Correlational design and purposive sampling technique were used on 285 samples for complainer and 230 for non-complainer residing in Selangor,Wilayah Persekutuan Kuala Lumpur and Putrajaya. Data were analysed by using Statistical Package for Social Sciences (SPSS) version 21 for exploratory factor analysis (EFA) and descriptive statistics while AMOS version 21 for structural equation modelling (SEM). Consistent with the outcome of EFA, the measurement model shows excellent fit for the complainers’ and non-complainers’ dataset and confirmed that CCB has four factors namely Public Complaint Soft Action (PCSA), Public Complaint Extreme Action (PCEA), Private Complaint Soft Action (PVSA) and Private Complaint Extreme Action (PVEA) for the complainers. For the noncomplainer,the result of the measurement model has identified two factors namely Private Complaint Soft Action (PVSA) and Private Complaint Extreme Action (PVEA). Both measurement models have met the required values for goodness-of-fit, average variance extracted (AVE) construct reliability and convergent validity. Fifteen hypotheses were developed to study the relationships among the variables for the complainers’ dataset and four hypotheses for the non-complainers.The results of the structural model explained PCSA, PCEA and PVSA have significant relationship with relationship quality for the complainers. Besides,the result also showed PCSA has significant relationship with SATCOM and SATCOM has significant relationship with relationship quality. For the noncomplainers,only PVSA shows significant relationship with relationship quality. Using bootstrapping technique, this study revealed that SATCOM mediated the relationship between PCSA and relationship quality.The ² difference test was used to assess the Effects of MPD as the moderator.The results confirmed that MPD moderated the relationship between PCSA,PCEA, PVSA and relationship quality. MPD also moderated the relationship between PCSA and SATCOM for the complainers’ dataset. For the oncomplainers,the result showed that MPD moderated the relationship between PVSA and relationship quality. The results proven that CCB onsists of four factors for complainer and two factors for non-complainers. Factors that are not extreme have significant relationship with relationship quality. The results also indicate the important of relationship quality and satisfaction with complaint handling in the relationship between the consumers and the service provider. As mobile phone services industry involved huge number of Malaysian population this issue should become the focal point to the parties concerned.